2002
DOI: 10.1051/limn/2002016
|View full text |Cite
|
Sign up to set email alerts
|

Rotifer diversity in a peat-swamp in southern Thailand (Narathiwas province) with the description of a new species ofKeratella Boryde St. Vincent

Abstract: We studied the rotifer fauna of one of the most pristine peat-swamps in the Southern Thai province of Narathiwas, To Daeng peat swamp. The samples yielded a total of sixty-seven rotifer species. Of these, three -Keratella mixta (Oparina-Charitonova), Lecane enowi Segers & Mertens and Monommata dentata Wulfert-are new to the Oriental region and the Thai fauna, one, Keratella taksinensis n. sp., is new to science. The fauna consists mainly of cosmopolitan {sensu lato) species, complemented by some Paleotropical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…The number of rotifers on record is highest in the northeastern part (275 species) (Sanoamuang et al, 1995;Savatenalinton, 1999, 2001;Segers et al, 2004;Savatenalinton and Segers, 2005), followed by the southern part (261 species) (Pholpunthin, 1997;Segers and Pholpunthin, 1997;Pholpunthin and Chittapun, 1998;Chittapun et al, 1999Chittapun et al, , 2002Chittapun et al, , 2003Chittapun et al, , 2005Chittapun et al, , 2007Chittapun and Pholpunthin, 2001;Segers and Chittapun, 2001;Sanoamuang, 2007;Meksuwun et al, 2011), the central part (182 species) (De Ridder, 1971;Koste, 1975;Sanoamuang and Segers, 1997;Jithland and Wongrat, 2006;Teeramaethee et al, 2006;Savatenalinton and Segers, 2008;Chittapun et al, 2009;Chittapun, 2011) and the northern part (115 species) (De Ridder, 1971;Sanoamuang, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of rotifers on record is highest in the northeastern part (275 species) (Sanoamuang et al, 1995;Savatenalinton, 1999, 2001;Segers et al, 2004;Savatenalinton and Segers, 2005), followed by the southern part (261 species) (Pholpunthin, 1997;Segers and Pholpunthin, 1997;Pholpunthin and Chittapun, 1998;Chittapun et al, 1999Chittapun et al, , 2002Chittapun et al, , 2003Chittapun et al, , 2005Chittapun et al, , 2007Chittapun and Pholpunthin, 2001;Segers and Chittapun, 2001;Sanoamuang, 2007;Meksuwun et al, 2011), the central part (182 species) (De Ridder, 1971;Koste, 1975;Sanoamuang and Segers, 1997;Jithland and Wongrat, 2006;Teeramaethee et al, 2006;Savatenalinton and Segers, 2008;Chittapun et al, 2009;Chittapun, 2011) and the northern part (115 species) (De Ridder, 1971;Sanoamuang, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…: Keratella valga tropica Apstein, 1907: Koste, 1975 24, 25, 26 52 Plationus patulus (Müller, 1786) N, NE, C, S 3, 4, 5, 7, 9, 10, 12, 13, 15, 17, 18, 20, 21, 22, 23, Syn: Brachionus patulus Müller, 1786: Boonsom, 1984 24, 26 Plationus patulus (Müller) f. typica: Sanoamuang et al, 199553 Platyias quadricornis (Ehrenberg, 1832 N, NE,C,S 3,4,5,7,9,10,13,15,17,18,21,22,23,24 Family Euchlanidae 84 Beauchampiella eudactylota (Gosse, 1886) N, NE, S 4, 9, 15, 17 Syn. : Manfredium eudactylotum (Gosse, 1886): Sanoamuang et al, 1995;Sanoamuang, 1998;Chittapun et al, 2002;Segers et al, 2004 To be continued on next page. 3,4,5,7,9,12,13,15,17,20,23,24,26 Incl.…”
Section: Species Distribution Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, Chittapun et al (1999) reported it from peat swamps in Phuket Province, Thailand. In 2001 Segers and Chittapun reported C. sanoamuangae again, this time as an interstitial rotifer, from the Malay Peninsula.…”
Section: Commentsmentioning
confidence: 99%